Comparison of 2 resident learning tools—interactive screen-based simulated case scenarios versus problem-based learning discussions: a prospective quasi-crossover cohort study - Rajan, Shobana; Khanna, Ashish; Argalious, Maged; Kimatian, Stephen J.; Mascha, Edward J.; Makarova, Natalya; Nada, Eman M.; Elsharkawy, Hesham; Firoozbakhsh, Farhad; Avitsian, Rafi (Journal of clinical anesthesia, 2016)
Simulation-based learning is emerging as an alternative educational tool in this era of a relative shortfall of teaching anesthesiologists. The objective of the study is to assess whether screen-based (interactive computer simulated) case scenarios are more effective than problem-based learning discussions (PBLDs) in improving test scores 4 and 8 weeks after these interventions in anesthesia residents during their first neuroanesthesia rotation. Prospective, nonblinded quasi-crossover study. Cleveland Clinic. Anesthesiology residents. Two case scenarios were delivered from the Anesoft software as screen-based sessions, and parallel scripts were developed for 2 PBLDs. Each resident underwent both types of training sessions, starting with the PBLD session, and the 2 cases were alternated each month (ie, in 1 month, the screen-based intervention used case 1 and the PBLD used case 2, and vice versa for the next month). Test scores before the rotation (baseline), immediately after the rotation (4 weeks after the start of the rotation), and 8 weeks after the start of rotation were collected on each topic from each resident. The effect of training method on improvement in test scores was assessed using a linear mixed-effects model. Compared to the departmental standard of PBLD, the simulation method did not improve either the 4- or 8-week mean test scores (P = .41 and P = .40 for training method effect on 4- and 8-week scores, respectively). Resident satisfaction with the simulation module on a 5-point Likert scale showed subjective evidence of a positive impact on resident education. Screen-based simulators were not more effective than PBLD for education during the neuroanesthesia rotation in anesthesia residency. •We evaluated the effects of 2 resident teaching tools on anesthesia residents' education during the neuroanesthesia rotation in this prospective quasi-crossover cohort study.•Problem-based learning discussion was compared with interactive screen-based simulation in improving test scores.•Each resident underwent both types of training sessions. Baseline tests were done (before the start of the rotation) based on the 2 clinical case scenarios.•Test scores 4 and 8 weeks after the start of the rotation were compared.•Compared to the current institutional standard of problem-based learning discussion, screen-based simulation did not improve test scores; however, resident satisfaction on a 5-point Likert scale showed positive impact on education.